VALUE CHAIN PALM OIL INDUSTRY ANALYSIS ON THE POLYOL POLYESTER PATHWAY - Adriana Sari Aryani; Yulian Syahputri; Hermawan Hermawan (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Palm oil is one of important Indonesia's export commodities. In 2017, the export value of palm oil and its derivatives (excluding oleochemicals and biodiesel) penetrated US $ 22.97 billion. The bright prospect of the palm oil commodity in the world vegetable oil trade encouraged the Indonesian government to develop an integrated palm oil industry. On the other hand, some downstream petrochemical products have begun to experience difficulties in raw materials, including Polyurethane. Polyurethane is a polymeric material from polyols and isocyanates which are widely used as packaging. Polyol itself is a polyether produced from the petroleum fraction. The polyol industry can be developed in the industrial tree branch of glycerol / glycerin in the large palm oil industry tree. Glycerin is generally the most end product of the palm oil fractionation industry, after cooking oil, margarine, shortening, and soap. In addition, glycerin is also a by-product of fatty acid esterification during biodiesel production. The value chain analysis carried out in the palm oil industry chain shows that polyol production has added new pathways that can extend the palm oil downstream industry chain. Analysis carried out on the main chain and the combined oil palm industry chain has been successfully used to map the polyol industry value chain on the palm oil track. The extension of the palm oil industry value chain on the polyol industry pathway can unite the industry with the chain of production of the petrochemical industry, in this case polyurethane, which at least can help substitute raw materials. A more detailed analysis of the perceptions of the role of the polyol industry in two directions, namely the palm oil industry chain with the polyurethane industry shows that there is a very large intersection of interests. Almost all perceptions of the role of key value chain activities in the polyurethane industry can be covered by the role of the value chain main activities in the palm oil polyol industry. Both value chains can be said to complement and complement each other. The production of polyester polyols can be absorbed by the needs of the polyurethane industry.